Entertainment is serious stuff: the politicisation of everyday laughs. Issue 3 (2nd September 2017) - Splendore, Sergio; Domaneschi, Lorenzo
ABSTRACT: The Italian media system is characterised by a high level of political parallelism, which is usually investigated in relation to journalism but rarely in relation to TV entertainment. This article offers an analysis of one of the most influential Italian infotainment shows, which usually deals with sensitive social and political events. The conceptual framework of the article is the one offered by the mediatization of politics. We present the findings of a media production analysis: we have spent four months observing the production process, and have carried out 12 in-depth interviews with persons who cover key roles as authors, directors and producers. Additionally, one month of news articles from dailies and periodicals archived by the TV programme's press office have been analysed. Even though the programme is broadcast by Berlusconi's network, its independence is rarely called into question. Its significance also lies in the failure of journalism itself to pursue its traditional objectives. The greatest legitimisation of the role of Striscia la Notizia in pursuing an alternative and independent agenda against politics derives precisely from newspapers themselves. Therefore, we conclude that the mediatization of politics – the fact that politicians and politics adapt themselves to the TV programme's logic and language – arises from the routines involved in its production; the role of a media system which not infrequently bases its agenda on the programme itself, and the needs of the politicians called upon to reply or defend themselves before sizeable audiences.